2019
DOI: 10.3390/coatings9010030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synthesis Conditions on the Controlled Growth of MgAl–LDH Corrosion Resistance Film: Structure and Corrosion Resistance Properties

Abstract: In this study, a series of MgAl–layered double hydroxide (LDH) thin films were synthesized by a single step hydrothermal process at different synthetic conditions on AA6082, and the combined effect of reaction temperatures and crystallization times on in situ growth MgAl–LDH structural geometry, growth rate, and more importantly on the corresponding corrosive resistance properties are briefly discussed. The synthesis of LDH was performed at reaction temperatures of 40, 60, 80, and 100 °C, while the treatment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…Coatings 2020, 9, Lastpage; doi: FOR PEER REVIEW www.mdpi.com/journal/coatings aggressive media, and this phenomenon is well correlated with the previous works [10][11][12][13] and for NiAl-LDHd a reduction of about 3-orders of magnitude in corrosion current density was observed compared to the substrate. Furthermore, the open circuit potential (OCP) is switched toward nobler values with structural variation from NiAl-LDHa to NiAl-LDHd, whilst a high corrosion potential of −0.18 V vs Ag/AgCl was observed for NiAl-LDHd, probably due to the formation of well-ordered platelet structure.…”
Section: Corrosion Behavior Of the Ldh Filmssupporting
confidence: 86%
See 3 more Smart Citations
“…Coatings 2020, 9, Lastpage; doi: FOR PEER REVIEW www.mdpi.com/journal/coatings aggressive media, and this phenomenon is well correlated with the previous works [10][11][12][13] and for NiAl-LDHd a reduction of about 3-orders of magnitude in corrosion current density was observed compared to the substrate. Furthermore, the open circuit potential (OCP) is switched toward nobler values with structural variation from NiAl-LDHa to NiAl-LDHd, whilst a high corrosion potential of −0.18 V vs Ag/AgCl was observed for NiAl-LDHd, probably due to the formation of well-ordered platelet structure.…”
Section: Corrosion Behavior Of the Ldh Filmssupporting
confidence: 86%
“…All the synthesized NiAl-LDHs films on AA6082 have shown lower corrosion current density along with a shift of the corrosion potential to higher values as compared to bare AA6082, however, NiAl-LDHd has shown the significantly reduced anodic and cathodic current density compared to the substrate and also from other developed NiAl-LDHs. It is also worthy to note that NiAl-LDHd has shown the relatively higher film thickness of around 35 µm, which may provide a comparatively better barrier film against the aggressive media, and this phenomenon is well correlated with the previous works [10][11][12][13] and for NiAl-LDHd a reduction of about 3-orders of magnitude in corrosion current density was observed compared to the substrate. Furthermore, the open circuit potential (OCP) is switched toward nobler values with structural variation from NiAl-LDHa to NiAl-LDHd, whilst a high corrosion potential of −0.18 V vs Ag/AgCl was observed for NiAl-LDHd, probably due to the formation of well-ordered platelet structure.…”
Section: Corrosion Behavior Of the Ldh Filmssupporting
confidence: 81%
See 2 more Smart Citations
“…Layered double hydroxides can be prepared by different methods such as coprecipitation, hydrolysis with urea, sol-gel, hydrothermal treatment, combustion and mechanical synthesis, among others, with the most common and economic method being coprecipitation [23][24][25]. Studies have reported that the synthesis method, the conditions of synthesis, the type of cations and structural anions, the metal precursors and the metal ratio M 2+ /M 3+ are determining factors on the properties and applications of LDH [26][27][28][29]. An important element to improve the catalytic activity of LDH is the thermal treatment to form mixed spinel-type oxides, specifically in the production of biodiesel by heterogeneous catalysis [30,31].…”
Section: Introductionmentioning
confidence: 99%